Developing the scale on discipline expectations of students: A validity and reliability study - Gülsen Özcan; Işıl Aktağ; Kaine Gülözer (Institute of Advanced Engineering and Science, 2020)
The study aimed to develop a valid and reliable scale to measure the expectations of students from the discipline program implemented in their schools. The study was conducted with students studying in seven different high schools in fall semester of 2019-2020 school year. As a result of the Confirmatory Factor Analysis (CFA), a 5-point Likert scale with 3 dimensions and 22 items was established. It was revealed that the fit index values for the final form of the scale are χ2 = 360.92, df = 206, P = 0.00, RMSEA = 0.062, GFI = 0.86, AGFI = 0.82, CFI = 0.93, RMR = 0.063; NNFI = 0.92. Cronbach Alpha reliability test was used to test the reliability of the ultimate scale and test retest reliability value was used to measure the stability of the test. Reliability value for the whole test was determined as .823, for the factor of Effective Teaching Discipline Expectation as 717, for the factor of Behavioral Discipline Expectation as 596, and for the factor of Social Discipline Expectation as .636. Test retest reliability of the test was determined as .763. Upon the evaluation of the analyses made, it was concluded that scale on discipline expectations of students is a valid and reliable scale to measure the discipline expectations of the students studying in secondary education institutions in Turkey.